2018
DOI: 10.1155/2018/3269847
|View full text |Cite
|
Sign up to set email alerts
|

A Rare and Potentially Catastrophic Infection: Primary Intestinal Aspergillosis—Case Report in an HIV Patient

Abstract: Aspergillus species are ubiquitous in nature; however, infection is uncommon, except in immunocompromised or immunosuppressed hosts. We present the case of a 71-year-old woman with a history of human immunodeficiency virus infection who presented with fever, weight loss, and diarrhea, posteriorly diagnosed with intestinal aspergillosis after examination of a segmental enterectomy piece. The diagnosis was made postmortem once the patient died after fast and progressive deterioration in the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Taken together, these studies suggest that direct application of fungicides for crop protection purposes may result in antifungal resistance that could theoretically constitute a threat to food safety especially in exposed immunocompromised individuals. While A. fumigatus is rarely implicated in fungal foodborne disease outbreaks, there have been reported cases of gastrointestinal aspergillosis due to ingestion of the pathogen in humans (CDC, 2014;Dias et al, 2018). Nevertheless, the paucity of studies and low prevalence reported are insufficient to confirm this use as an important threat to consumers.…”
Section: Arb In Human Pathogens and Phytopathogensmentioning
confidence: 99%
“…Taken together, these studies suggest that direct application of fungicides for crop protection purposes may result in antifungal resistance that could theoretically constitute a threat to food safety especially in exposed immunocompromised individuals. While A. fumigatus is rarely implicated in fungal foodborne disease outbreaks, there have been reported cases of gastrointestinal aspergillosis due to ingestion of the pathogen in humans (CDC, 2014;Dias et al, 2018). Nevertheless, the paucity of studies and low prevalence reported are insufficient to confirm this use as an important threat to consumers.…”
Section: Arb In Human Pathogens and Phytopathogensmentioning
confidence: 99%
“…Past reports indicate infections caused by Acremonium species, although rare, affect immunocompetent individuals by colonizing the lungs and gastrointestinal tract ( 51 ). Clinical case studies in immunosuppressed patients have reported the ability of Aspergillus infections to develop into serious gastrointestinal complications including enterocolitis, appendicitis, colonic ulcers, and gastrointestinal bleeding ( 47 , 136 ). Although the microbial composition of SFD has been characterized, the pathological features and mechanisms of SFD that are responsible for intestinal barrier dysfunction during chronic exposure remain an understudied area of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, gut-derived metabolites can pass systemically to the bone marrow and promote hematopoiesis ( 137 , 173 ). Under inflammatory conditions, hematopoietic stem cells can differentiate and give rise to dendritic cell precursors that disseminate to the lungs and mature into CD11b + dendritic cells ( 21 , 136 , 172 ) that have been shown to be responsible for inducing allergic airway hypersensitivity ( 174 ). SCFAs can also affect lung immunity by enhancing CD8 + T-cell activity ( 22 ), promoting forkhead box P3 (FOXP3) expression ( 175 ) and regulating the production of proinflammatory cytokines (TNF-α, IL-2, IL-6, IL-10) through the activation of free fatty acid receptor 3 ( 122 , 176 ).…”
Section: Introductionmentioning
confidence: 99%